(3EOGQI GdLhOI aj eTGQjY GdhbGjI ef GdLQjeI (B=s Quality in crime prevention : (3bQGAI aj ChQGb eDJeQ HjcGQjG GdChd ddLhOI aj eLGd GdhbGjI ef GdLQjeI (B: "(3QDi dLhOI CaVd ddhbGjI ef GdLQjeI(B" /s - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3hRGQI GdOGNdjI, GdbjGOI GdYGeI dTQWI GdTGQbI, EOGQI eQcR HMhK GdTQWI, s, 2015)
(3jJfGhd gPG GdcJGH GSJYQGVG deHGOF EOGQI GdLhOI aj eHGOQGJ heTGQjY GdhbGjI ef GdLQjeI hHQZe ef GNJdGa GdCHMGK hGdOQGSGJ GdeJYdbI HChQGb GdYed GdJj bOeJ aj eDJeQ HjcQjQ GdChd ddLhOI aj eLGd GdhbGjI ef GdLQjeI EdG CfgG gOaJ LejYG Edi JbOje QDi dLhOI CaVd ddhbGjI ef GdLQjeI, hbO QcRJ LejY gPg GdChQGb Edi Cf EOGQI GdLhOI dgG CgejJgG aj eLGd eHGOQGJ heTGQjY GdhbGjI ef GdLQjeI ceG Cf gPG GdcJGH QHeG jchf Chd eQLY HGddZI GdYQHjI jJfGhd EOGQI GdLhOI aj eLGd eJNUU ceLGd GdLQjeI hbO QcRJ LejY GdChQGb hCHMGK GdJj Je GSJYQGVgG aj gPG GdcJGH Edi Cf GdfJGFL GdeJMbbI gj GdJj JHQR GdLhOI aj Cj fTGW eJYdb HGdhbGjI ef GdLQjeI hJYR ZGdHG GdfJGFL GdLjOI Edi GdEOGQI GdLjOI deHGOQGJ GdhbGjI ef GdLQjeI hdbO JHfJ GdChQGb LejYG eYGjjQ HjcQjQ HGYJHGQgG CfgG GdVeGf GdCeKd deHGOQGJ eTGQjY efY GdLQjeI(B.s
Keywords: (3ecGaMI GdLQjeIs -- (3eDJeQGJs; (3GdLQjeI hGdeLQehfs -- (3eDJeQGJs; (3EOGQI GdLhOI GdTGedIs -- (3eDJeQGJs